Common Base Four-Finger InGaAs/InP Double Heterojunction Bipolar Transistor with Maximum Oscillation Frequency 535 GHz*Supported by the National Basic Research Program of China under Grant No 2011CB301900, and the Natural Science Foundation of Jiangsu Province under Grant Nos BK2011010 and BY2013077. (July 2015) - Niu, Bin; Wang, Yuan; Cheng, Wei; Xie, Zi-Li; Lu, Hai-Yan; Chang, Long; Xie, Jun-Ling
<x content-type="archive" xml:space="preserve">Abstract</x> A common base four-finger InGaAs/InP double heterojunction bipolar transistor with 535 GHz fmax by using the 0.5 μm emitter technology is fabricated. Multi-finger design is used to increase the input current. Common base configuration is compared with common emitter configuration, and shows a smaller K factor at high frequency span, indicating a larger breakpoint frequency of maximum stable gain/maximum available gain (MSG/MAG) and thus a higher gain near the cut-off frequency, which is useful in THz amplifier design.